How Individual Scholars Can Reduce the Rigor-Relevance Gap in Management Research - Joachim Wolf; Timo Rosenberg (BuR - Business Research, 2012)
This paper discusses a number of avenues management scholars could follow to reduce the existing gap between scientific rigor and practical relevance without relativizing the importance of the first goal dimension. Such changes are necessary because many management studies do not fully exploit the possibilities to increase their practical relevance while maintaining scientific rigor. We argue that this rigor-relevance gap is not only the consequence of the currently prevailing institutional context in the scientific system, but that individual scholars can reduce the gap between rigorous and practically relevant research by modifying their research work. Thus, most of our suggestions refer to individual scholars research activities and relate to specific steps in the (empirical) research process. Our discussion does not imply that all management studies should be practically oriented; basic research will remain a very important part of management research. However, we believe that not enough management research studies are significantly influenced by practical relevance.
urn:nbn:de:0009-20-35051
Keywords: 650; management; practical relevance; rigor; empirical research; Operations Research; Theorie-Praxis-Verhältnis; Wissenschaftsforschung